2019
DOI: 10.1186/s12876-019-1010-4
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota transplantation for ulcerative colitis: a prospective clinical study

Abstract: Background: Fecal microbiota transplantation may contribute to disease remission in ulcerative colitis; however, the factors that determine the effects of treatment remain unknown. The aim of the present study was to prospectively investigate the clinical efficacy of fecal microbiota transplantation in patients with ulcerative colitis and identify the bacterial signatures associated with clinical remission.Methods: A total of 20 patients with ulcerative colitis were included in this prospective and uncontrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 22 publications
4
39
0
1
Order By: Relevance
“…The present study demonstrated that three rounds of FMT (13,(28)(29)(30). The improved efficacy displayed in the present study may be explained by the modified FMT procedures used, including stool preparation (feces exposure to air for <30 min), microbiota resource (fresh; all FMTs for one patient were derived from the same donor), delivery route (via TET tube; remained in the right lateral position for 30 min to maintain the largest contact area between microbiota and intestines), dosage (150 ml to avoid inducing intestinal peristalsis) and intensity (three times within one week).…”
Section: Discussionsupporting
confidence: 57%
“…The present study demonstrated that three rounds of FMT (13,(28)(29)(30). The improved efficacy displayed in the present study may be explained by the modified FMT procedures used, including stool preparation (feces exposure to air for <30 min), microbiota resource (fresh; all FMTs for one patient were derived from the same donor), delivery route (via TET tube; remained in the right lateral position for 30 min to maintain the largest contact area between microbiota and intestines), dosage (150 ml to avoid inducing intestinal peristalsis) and intensity (three times within one week).…”
Section: Discussionsupporting
confidence: 57%
“…Both studies [ 16 , 17 ] used individual stool donation, which means that each donor provided a stool for one, at most two recipients. Tian et al [ 41 ] even described non-significantly decreased Shannon and Chao indices after FMTs, but still observed positive clinical outcomes and improved symptoms in the patient with UC. The same authors [ 41 ] did not find differences in beta diversity; however, in our study, statistically significant results were obtained from pairwise PERMANOVA analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Tian et al [ 41 ] even described non-significantly decreased Shannon and Chao indices after FMTs, but still observed positive clinical outcomes and improved symptoms in the patient with UC. The same authors [ 41 ] did not find differences in beta diversity; however, in our study, statistically significant results were obtained from pairwise PERMANOVA analyses. Jaccard distances between samples revealed the separation of responders and non-responders after FMT treatment, however, the high variability of samples within the FMT group analyzed in this work has to be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Mahajan et al described FMT efficacy in reducing adverse effects of corticosteroid therapy, for example weight loss (from BMI 28.0 kg /m 2 to 23.5 kg /m 2 without diet modifications), reducing hair loss, backache, morning stiffness and allergic rhinitis after 22 weeks of 7 FMT sessions [23]. Other studies demonstrated that FMT could reduce disease symptoms, for example diarrhea, stomach ache and blood in the stool, however decrease of C-reactive protein level was not observed [24]. The FMT method showed efficacy in treatment-resistant UC as well and clinical, endoscopic and laboratory remission was observed in 43.3% patients [25].…”
Section: The Use Of Fmt In Ulcerative Colitismentioning
confidence: 99%